SCREENING FOR ANTIPROLIFERATIVE ACTIVITY OF A CRUDE ACETONE EXTRACT OF SENNA SPP ON HL-60 AND WIL-2 NS CELL LINES - Ngobeni, A.; Mokgotho, M. P.; Masoko, P.; Howard, R. L.; Mampuru, L. J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
For many decades plants have provided mankind with herbal remedies against many infectious diseases. Cancer is one of the major public health problem in many developed countries. Senna species falls under the Fabaceae family and are well known for their therapeutic properties. They are being used as plant herbs in many countries including South Africa. The acetone crude extract prepared from the roots of Senna sp was investigated for its cytotoxic activity against two cell lines, HL-60 promyelocytes and WIL-2 NS lymphocytes cells. The changes in nuclear morphology brought by the extract on these cells were also investigated. To investigate the cytotoxicity of the extract, cells were treated with concentrations varying from 0-200 µg/ml for 72 hours and samples collected at 24 hours interval to evaluate cell proliferation and viability using the trypan blue dye exclusion method. The extract was shown to inhibit the proliferation of both HL-60 and WIL-2 NS; with WIL-2 NS being more sensitive to the treatment as compared to HL-60 cells. The nuclear morphological changes of the treated HL-60 and WIL-2 NS cells showed characteristics that are associated with apoptotic features. This could mean that the extract inhibited the proliferation of the cells through the programmed cell death pathway.Acknowledgements: University of Limpopo senate research fund, NRF